Impacts of breaching planetary boundaries on human health: Current and future threats - Ricky Anak Kemarau; Zaini Sakawi; Oliver Valentine Eboy; Wan Shafrina Wan Mohd Jaafar; Zulfaqar Sa'adi; Stanley Anak Suab (GeoHealth, 2025)
This review examines the impact of breaching planetary boundaries on human health and potential future threats, emphasizing the need for effective mitigation and adaptation strategies. Through a rigorous literature review of 142 high‐quality articles, we explore the health implications of breaching planetary boundaries such as climate change, land system change, biodiversity loss, biogeochemical flows, aerosol loading, stratospheric ozone depletion, freshwater use, novel entities, and ocean acidification. Our findings indicate a direct association between breached planetary boundaries and a range of health risks, including respiratory and cardiovascular diseases, increased infectious disease vulnerability, and nutritional impacts due to compromised food sources. The analysis highlights the disproportionate effects on vulnerable populations and underscores the significance of localized and global strategies in mitigating these health threats. Effective measures, including urban planning for green spaces and pollution control, have been identified as crucial. The review calls for an integrated, interdisciplinary approach to safeguard human health against the backdrop of environmental degradation, stressing the urgency of global collaboration in policy development and implementation.